EFEKTIVITAS PENGGUNAAN WHEY KEFIR TERHADAP KUALITAS ORGANOLEPTIK DAGING DADA AYAM PETELUR AFKIR (Gallus gallus): EFEKTIVITAS PENGGUNAAN WHEY KEFIR TERHADAP KUALITAS ORGANOLEPTIK DAGING DADA AYAM PETELUR AFKIR (Gallus gallus) - Zakly, Fariz; Anggraeni; Haryanto, Agung Puji (Jurnal Peternakan Nusantara, 2024)
Low tenderness and fishy aroma are suspected to be the reasons making consumers have low acceptance of spent layer hen meat. The use of kefir whey, a clear liquid obtained from kefir making process, is a way to improve the quality of this meat. Kefir is a product resulted from the fermentation of milk by using lactic acid bacteria (LAB), acetic acid bacteria, and yeast. This study was aimed at assessing the effectiveness of the use of kefir whey in improving the organoleptic quality of spent layer hen meat. The study was conducted at Balai Besar Pelatihan Kesehatan Hewan Cinagara, Bogor and the Biology Laboratory of Djuanda University, Bogor, in February 2023. A total of 120 breast meat pieces sized 2 cm x 2 cm of spent layer hen aged 80 weeks were used as samples. These meat samples were randomly allocated into treatments of kefir whey soaking in a completely randomized design with 4 treatments and 5 replicates. Treatments consisted of soaking solutions including no soaking solution (P0, control), 5 ml kefir whey + 95 ml distilled water (P1), 10 ml kefir whey + 90 ml distilled water (P2), and 15 ml kefir whey + 85 ml distilled water (P3). Measurements were taken on meat aroma, tenderness, color, taste, and juiceness. Data were subjected into a Kruskall Wallis test and an analysis of variance test. Results showed that no significant effects of treatments (P>0.05) on meat color, taste, and juiceness. However, meat tenderness in hedonic test and meat aroma and tenderness in hedonic quality test were found to be different (P<0,05) it was concluded  that soaking the meat in a soaking solution containing kefir whey by up to 5 mlimproved the tenderness (hedonic test) and aroma an tenderness(hedonic quality test) of spent layer hen breast meat.